Pippi Longstocking - Lindgren, Astrid, 1907-2002 (New York Puffin Books, 1997)
Escapades of a lucky little girl who lives with a horse and a monkey-- but without any parents-- at the edge of a Swedish village.
Include Illustration
Keywords: SwedenLongstocking, Pippi -- Sweden -- Humorous stories